Fertilizer demand and profitability amid global fuel-food-fertilizer crisis: Evidence from Ethiopia - Assefa, Thomas; Berhane, Guush; Abate, Gashaw T.; Abay, Kibrom A. (Elsevier, 2025)
We assess fertilizer demand and profitability in Ethiopia in the face of the recent global fuel–food–fertilizer price crisis and other domestic shocks. We first examine farmers’ response to changes in both fertilizer and food prices by estimating price elasticity of demand. We then evaluate the profitability of fertilizer by computing average value–cost ratios (AVCRs) associated with fertilizer application before and after these crises. We use detailed longitudinal household survey data collected in three rounds, covering both pre-crisis (2016 and 2019) and post-crisis (2023) production periods, focusing on three main staple crops in Ethiopia (maize, teff, and wheat). Our analysis shows that fertilizer adoption, and yield levels were increasing until the recent crises, but these trends have been halted by these crises. We also find slightly larger fertilizer price elasticity of demand estimates than previous estimates, ranging between −0.40 and −1.12, which vary across crops. We find that farmers are more responsive to fertilizer prices than to output prices. Farmers’ response to increases in staple prices was statistically insignificant and hence not as strong as theoretically perceived. Households with smaller farm sizes are relatively more responsive to changes in fertilizer prices. Finally, we show important dynamics in the profitability of chemical fertilizer. While the AVCRs show profitable trends for most crops, the share of farmers with profitable AVCRs declined following the fertilizer price surges. Our findings offer important insights for policy focusing on mitigating the adverse effects of fertilizer price shocks.